Avoidance behaviour of Rattus rattus to odours of eucalyptus and citronella oils under maze experiments: Eucalyptus and citronella oils as repellents - Singla, Neena; Thind, Ramandeep Kaur (Annals of Arid Zone, 2023)
Substances that make animals move away from the source are called repellents. It may be an object, a device or a chemical substance which by touch, sound, color, taste or odor will ward off the animal or prevent an animal from feeding or gnawing. In multi-choice T-maze experiments, the behavior of male and female house rat (Rattus rattus) was recorded in response to the odors of 5% eucalyptus and 5% citronella oils released through encapsulated wax blocks. A significant (P ≤0.05) difference in values of different parameters related to distance moved, velocity and frequency of movement was observed between untreated zone and the zones treated witheucalyptus and citronella oils indicating avoidance behavior of rats in response to the odors from eucalyptus and citronella oils. The record of animal tracks in different zones of T-maze also revealed reduced movement and activity of the rats in treated zones. No significant difference was observed between behavior of male and female rats. These experiments suggested the use of two oils in repelling the rats away from enclosed store houses.